Sex and COVID-19 vaccination uptake and intention in the Democratic Republic of Congo, Nigeria, Senegal, and Uganda - Ndejjo, Rawlance; Chen, Nuole; Kabwama, Steven N.; Bamgboye, Eniola A.; Bosonkie, Marc; Bassoum, Oumar; Kiwanuka, Suzanne N.; Salawu, Mobolaji M.; Egbende, Landry; Sougou, Ndeye Mareme; Afolabi, Rotimi F.; Leye, Mamadou Makhtar Mbacké; et al. (Frontiers in Global Women's Health, 2024)
The introduction of vaccines marked a game changer in the fight against COVID-19. In sub-Saharan Africa, studies have documented the intention to vaccinate and the uptake of COVID-19 vaccines. However, little is documented about how sex differences could have impacted COVID-19 vaccination. We conducted a multi-country cross-sectional study to assess the sex differences in COVID-19 vaccine uptake and intention to vaccinate in the Democratic Republic of Congo (DRC), Nigeria, Senegal, and Uganda. This study involved analysis of data from mobile surveys conducted between March and June 2022 among nationally constituted samples of adults in each country. Bivariate and multivariable logistic regression models were run. The self-reported uptake of COVID-19 vaccines was not significantly different between males and females (p = 0.47), while the intention to vaccinate was significantly higher among males (p = 0.008). Among males, obtaining COVID-19 information from health workers, testing for COVID-19, and having high trust in the Ministry of Health were associated with higher vaccination uptake. Among females, having high trust in the government was associated with higher vaccination uptake. For intention to vaccinate, males who resided in semi-urban areas and females who resided in rural areas had significantly higher vaccination intention compared to their counterparts in urban areas. Other factors positively associated with vaccination intention among males were trust in the World Health Organization and perceived truthfulness of institutions, while males from households with a higher socio-economic index and those who had declined a vaccine before had a lower vaccine intention. Overall, the factors differentiating vaccine uptake and intention to vaccinate among males and females were mostly related to trust in government institutions, perceived truthfulness of institutions, and respondent's residence. These factors are key in guiding the tailoring of interventions to increase COVID-19 vaccine uptake in sub-Saharan Africa and similar contexts.